KAJIAN KOMPOSISI KIMIA AMPAS KEDELAI HASIL SAMPING PENGOLAHAN KECAP - Sri Susanti (BUANA SAINS, 2006)
The research was conducted from May-June 2004 at the Ketchup “Kinking” Factory Turban regency. The aim of the research was to study of food substance content or soy dregs chemical composition from two methods of ketchup making. Method used in this research was a case study. Soy dregs from two methods of ketchup making, i.e. fermentation (F) and sangria (S) were used in this research. Proximate analysis was conducted at the Laboratory of Animal Feed and Nutrition, Animal Husbandry Faculty, Brawijaya University Malang, and amino acid analysis was conducted at the Laboratory of Food Processing Balitbangtan, Bogor Regency. The results showed that the soy dregs from fermentation method (F) had a greater composition than that of sangrai method (S), with a complete amino acid content. So that, the soy dregs from fermentation method performed a good feed source for avian and non ruminant animals